Neuroplasticity of the extended amygdala in opioid withdrawal and prolonged opioid abstinence - Kaplan, Gary B.; Thompson, Benjamin L. (Frontiers in Pharmacology, 2023)
Opioid use disorder is characterized by excessive use of opioids, inability to control its use, a withdrawal syndrome upon sudden discontinuation, and long-term likelihood of relapse. The behavioral stages of opioid addiction correspond with affective experiences that characterize the opponent process view of motivation. In this framework, active involvement is accompanied by positive affective experiences which gives rise to "reward craving," whereas the opponent process, abstinence, is associated with the negative affective experiences that produce "relief craving." Relief craving develops along with a hypersensitization to the negatively reinforcing aspects of withdrawal during abstinence from opiates. These negative affective experiences are hypothesized to stem from neuroadaptations to a network of affective processing called the "extended amygdala." This negative valence network includes the three core structures of the central nucleus of the amygdala (CeA), the bed nucleus of the stria terminalis (BNST), and the nucleus accumbens shell (NAc shell), in addition to major input from the basolateral amygdala (BLA). To better understand the major components of this system, we have reviewed their functions, inputs and outputs, along with the associated neural plasticity in animal models of opiate withdrawal. These models demonstrate the somatic, motivational, affective, and learning related models of opiate withdrawal and abstinence. Neuroadaptations in these stress and motivational systems are accompanied by negative affective and aversive experiences that commonly give rise to relapse. CeA neuroplasticity accounts for many of the aversive and fear-related effects of opiate withdrawal via glutamatergic plasticity and changes to corticotrophin release factor (CRF)-containing neurons. Neuroadaptations in BNST pre-and post-synaptic GABA-containing neurons, as well as their noradrenergic modulation, may be responsible for a variety of aversive affective experiences and maladaptive behaviors. Opiate withdrawal yields a hypodopaminergic and amotivational state and results in neuroadaptive increases in excitability of the NAc shell, both of which are associated with increased vulnerability to relapse. Finally, BLA transmission to hippocampal and cortical regions impacts the perception of conditioned aversive effects of opiate withdrawal by higher executive systems. The prevention or reversal of these varied neuroadaptations in the extended amygdala during opiate withdrawal could lead to promising new interventions for this life-threatening condition.